INTERNATIONAL COLLABORATION: STRENGTHENING ADOLESCENT HEALTH PROGRAMS THROUGH GLOBAL PARTNERSHIPS IN EMPOWERING SCHOOL HEALTH PROGRAM CADRES AND PEER TUTORS - Wittiarika, Ivon Diah; Jayanti, Ratna Dwi; Andriyanti; Dewi Setyowati; Riri Aprianti; Nenccy Mirasari; Sumbawati, Mulia Dian; Siti Nurul Komariah; Deby Artika P; Pupus Ultraluana; Ngatwati; Yublina Rambu Mbali Idi; Nurhayati Fitria Amin; Mohamed Alif Haikal Bin Mohamed Iskandar; Fatin Nazurah Izzati Binti Hamdani; Siti Norhikmah Binti Abd. Razak (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
This study focuses on the importance of reproductive health education for adolescents as an effort to improve knowledge and attitudes in facing puberty and mental health. Adolescents, aged 10-19 years according to WHO and 10-18 years according to the Indonesian Ministry of Health, are in a critical transition period that affects their physical, mental and social health. Lack of knowledge about puberty and how to deal with it can have a negative impact on reproductive health, including the risk of anemia, obesity, and mental health problems experienced by more than a third of adolescents in Indonesia. As a solution, Adolescent Posyandu was implemented at SMP Negeri 57 Surabaya by involving Student Health Unit (UKS) cadres as peer tutors. This activity is a collaboration between the Midwife Professional Education Study Program of the Faculty of Medicine, Universitas Airlangga, Siwalankerto Health Center and the University of Brunei Darussalam, was carried out on November 8, 2024 and attended by 26 students. The program consisted of five stages of service: registration, health checks (blood pressure, weight, height, upper arm circumference (LiLA), abdominal circumference (LP)), recording, nutrition in health education, and counseling. In addition, counseling on puberty, nutrition, and mental health was delivered through educational games to improve the cognitive, affective, and psychomotor aspects of adolescents. The results showed an increase in participants' understanding of physical changes during puberty, the importance of nutrition, and the important role of peers in supporting mental health through educational games. UKS cadres are expected to act as pioneers in disseminating the information and knowledge gained to their peers, thus creating a school environment that supports adolescent health. The long-term positive impact is expected to contribute to the achievement of the 3rd Sustainable Development Goals (SDGs), namely ensuring healthy lives and well-being for all ages by 2030. The implementation of the program went smoothly with the support of the Puskesmas and the school, demonstrating the effectiveness of the peer education approach in improving adolescent health status.